English Communication in Tourism: A Qualitative Study on Applied Linguistics and Tour Guides - I Nengah Laba; Ni Putu Veny Narlianti (Soshum: Jurnal Sosial dan Humaniora, 2025)
Bali's tourism industry heavily relies on international visitors, making English proficiency essential for tour guides who serve as cultural ambassadors. This qualitative study examines the relationship between applied linguistics principles and the English communication skills of tour guides at PT. Indo Bali Tours. Through semi-structured interviews and observations, the study explores key linguistic aspects, including vocabulary usage, discourse structuring, and pragmatic competence. Findings indicate that a lack of specialized tourism vocabulary often leads to oversimplification of complex cultural and historical narratives. Additionally, language anxiety negatively impacts fluency and engagement. These insights underscore the need for structured, tourism-specific language training programs that integrate applied linguistics principles to enhance communication effectiveness. By bridging the gap between applied linguistics and the tourism industry, this study offers practical recommendations for improving English proficiency among tour guides, ultimately enriching the visitor experience.